Fabrication and characterization of polylactic acid/hyaluronic acid/collagen nanofibers for tendon tissue engineering - ULAĞ, SONGÜL (My University, 2023)
Tendon tissue engineering aims to integrate engineered, functional replacements with their native counterparts in order to repair tendon injuries. Responsible for body movement and stabilization of the joint structure, tendons stand out with their superior biomechanical properties. Collagen 1 (COL) is the main component that contributes these properties to the tendon structure organized in hierarchical bundles. Hyaluronic acid (HA) participates in the formation of the tendon extracellular matrix and enhances the viscoelasticity of the structure. Polylactic acid (PLA) is widely used in tendon tissue engineering due to its biocompatibility, biodegradability and mechanical properties. Therefore, a novel PLA/HA/COL hybrid scaffold was designed and fabricated by electrospinning for the repair of tendon defects. While 10% PLA is used as the control group, 4 scaffolds containing 1% HA and/or 1% COL were fabricated. One of the scaffolds was produced by coaxial electrospinning: the inner layer consists of 10% PLA and 1% COL, while the composition of the outer layer is 10% PLA and 1% COL. The morphological, thermal, chemical, and mechanical properties of the tendon scaffolds were evaluated using SEM, DSC, FT-IR, swellingdegradation test, and tensile testing test, respectively. In vitro cell culture experiments were performed on mesenchymal stem cells using MTT method. It is anticipated to confirm that PLA/HA/COL scaffolds promote cell adhesion, proliferation, and regeneration by characterisation and in vitro cell culture results.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)